Regulating government (s share): The fifty-percent rule of the Federal Constitutional Court in Germany - Andreas von Arnauld; Klaus W. Zimmermann (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2010)
Some numbers in the political sphere seem to be chosen rather arbitrarily. One example might be the rule set out by the Second Senate of the German Federal Constitutional Court in 1995 that the overall tax load on assets must be limited to 50% of the yield on those assets. This rule was understood by many as a general principle for taxation. The article first sketches the socio-political climate under which the rule originated: a rise of neo-liberal thought met with the inability of the political institutions to reform the German welfare state with its evergrowing expenses. The Constitutional Courts intervention is interpreted as a reaction to this stagnation in politics. An analysis from the perspective of Constitutional Law, however, reveals that the fifty-percent rule cannot be convincingly based on the German Basic Law, and instead must be seen as a political move of the Court. But this move did not follow an economic rationality, either; for an optimal governments share can only be determined in relation to the economic performance of a country and not by fixing it generally at a maximum of 50% of GDP. The demise of the fifty-percent rule already began four years later. In 2006, finally, the Senate moved away from the individual rights-based approach of 1995 to a more general assessment, taking also into account an increasingly globalized tax competition. The reason for this clear-cut change in the Courts juris-prudence can be found in a change of the socio-political and institutional parameters, thus witnessing to the effect of the political climate on court decisions. The analysis also shows that the rule was created and abandoned only on the basis of an introverted legal discussion, economic arguments hardly playing any role in the process. The new line of the Senate, however, might guarantee for a better integration of economic science into tax policy by exchanging fixed limits for a 'discursive' model, demanding from the tax legislator better reasons for higher taxes.
urn:nbn:de:gbv:705-opus-24584
Keywords: H11; H24; K34; P16; 330; fifty-percent rule; constitutional decisions; optimal governments share; Steuerbelastung; Rechtsprechung; Verfassungsgericht; Staatsquote; Public Choice; Deutschland